PMO-151 Excellent disease free and overall survival rates after long term follow-up of a cohort of injecting drug users treated for HCV. (28th May 2012) - Lewis, H; Wilkinson, M; Dalton, J; Gardner, H; Hothi, J; Ibrahim, N; King, K; Mirza, M; Tippett, A; Turton, J; Woods, C; Wynne, S; et al.
Abstract : Introduction: Hepatitis C virus (HCV) is common in injecting drug users (IDU's), but <10% of those known to be infected are currently treated. Antiviral therapy for injecting drug users with HCV in North East London is provided by a Blood Borne Virus nursing team based in community outreach clinics. We aimed to examine HCV and drug related outcomes in patients treated by this service. Methods: A retrospective notes analysis was performed of all patients treated between September 2006 and June 2011. Data were collected on demographics, HCV treatment, health and social outcomes. Minitab 16 and Prism 5 were used to perform statistical analysis. The Wilcoxon signed rank test, unpaired T test, and Mann–Whitney test were used to analyse drug and alcohol and demographic outcomes. Results: 152 patients were treated. 77 were active IDU's and 75 were ex-IDU's. 80% were male. 45% were genotype 1, 54% were genotype 2 or 3. 81% of patients were compliant with treatment. 105 patients (69%) achieved an end of treatment response (ETR) Sustained viral response (SVR) rate was 58%. Overall survival post SVR was 100% and HCV free survival was 98%. Two patients were re-infected at 14 and 51 months after treatment (See Abstract PMO-151 figure 1 ) five deaths occurred 21, 32, 35, 37 and 44 months after treatment finished. All deaths were in non-responders. No deaths were attributable to treatment. There was no significant difference in demographics or treatment outcomes between active and ex-IDU's. Full data on heroin injection use was available in 133 patients, crack use in 58 patients and alcohol in 72 patients. Overall heroin injection use pre- and post-treatment reduced from 51% of patients to 38% (p<0.0001), crack use reduced from 34% to 19% (p<0.0001), and alcohol use from 38% to 32% (p=0.0035). Conclusion: This is the largest study published to-date examining the impact of antiviral therapy in patients actively using illicit drugs. Of importance long term follow-up data showing low re-infection rates, a significant reduction in illicit drug use after therapy and excellent disease free and overall survival in patients who achieve SVR is presented. Our findings confirm previous, small scale studies showing that effective treatment for injectors is possible within the appropriate clinical setting. Competing interests: None declared.